Distintividade marcária - Carvalho, Carlos Eduardo Neves de (2015)
This essay is dedicated to the study of two empiric phenomena resulting from the use of the mark in the consumer market: acquisition and loss of trademark distinctiveness. The first part is dedicated of the study of acquisition of trademark distinctiveness which could happen in two possibilities: secondary meaning and notoriety. First of all, is addressed the distinctiveness, as the main trademark function and its condition of validity for granting the trademark registration. In the first case, the acquisition of distinctiveness of a trademark occurs by the factual phenomenon known as secondary meaning, in which a descriptive sign, apparently not distinctive, through its prolonged use on the market, acquired a secondary meaning as a distinctive brand, being therefore susceptible for trademark registration. In the second type of acquired distinctiveness, a common trademark can become notorious, renowned and with high commercial prestige within the consumer market through the trademark owner´s advertising investments, which receives special trademark protection: well-known mark within its commercial activity branch, and famous mark, which receives legal protection in all classes of goods and services. The Second Part of this work is dedicated to the study of the loss of distinctiveness of a trademark which may occur in two situations: genericism and dilution. The first situation, genericism, is the factual phenomenon opposed to the secondary meaning, in which, the trademark owner's behavior to promote its brand, results into semantic synonymous and descriptive of the product or service marked by the renowned trademark. The second situation of the loss of trademark distinctiveness is called the dilution phenomenon, which can occurs in three situations: the improper use of a high-renowned trademark in different goods and services marked by the original brand (blurring), the harm to a high-renowned trademark reputation (tarnishment) and the disparagement of a high-renowned trademark in promotional campaigns made by competitors